PERANCANGAN MEDIA PEMBELAJARAN PADA ALAT PEMANTAU KUALITAS UDARA BERBASIS WEBSITE - Muhammad Rizqi Prayogo; Yuyun Suprapto; Rifdian I.S (Politeknik Penerbangan Surabaya, 2022)
The life of cadets at Aviation Polytechnic of Surabaya involves a tight schedule and activities such as classroom learning and dormitory engagements that influence the surrounding air quality. The aim of this research is to provide users with information about the air quality at Aviation Polytechnic of Surabaya using Internet of Things technology. The research method employed is the 4D development method. Based on the research results, the product validation achieved a consistent score of 96.3%, with the note that it can be used with some revisions. The CO gas level indicates a value of <12, and the CO2 level shows a value of <175, ensuring that both gases remain within safe limits and do not exceed reference values. Temperature and humidity readings with the smallest differences indoors occur in the evening (0.1°C), and humidity shows the same outcome (0%). Outdoors, temperature readings with the smallest difference occur in the afternoon (0.5°C), while humidity variations are most pronounced in the morning (3.4%).